THE EFFECT OF THE USE OF BIRTHING BALL ON PAIN REDUCTION IN WOMEN IN PMB YUYU YULIYATI, S. ST - Ayu Idaningsih; Yuyun Wahyu; Mitha Annisa Royani (International Journal Labs, 2022)
Introduction. Pain in labor can be overcome pharmacologic and non-pharmacologic to prevent excessive pain. One effort to reduce pain in labor is to use the birthing ball technique. Destinations. This study aims to determine the effect of using the birthing ball technique on reducing pain in labor. Methods. In this study, the researcher used a pre-experimental research design using a one-shot case study design. The sample of this study was 15 people according to the interpretation of childbirth carried out in March - May 2022 at PMB Yuyu Yuliyati S.ST. Univariate and bivariate analysis in this study used computer assistance with a software program (SPSS). Results and Conclusions. The results showed that the pain scale before the birthing ball was done on average 6.93 and after the birthing ball was done the average was 4.60. This shows the effect of the use of birthing balls on reducing pain in mothers giving birth at PMB Yuyu Yuliyati, S. ST with (p-value = 0.00).. In this study, it was proven that the use of birthing balls in laboring mothers had an effect on reducing pain, so the use of birthing balls could be used as complementary midwifery care in the labor process as an effort to reduce pain during labor and can add knowledge and insight and can be used as a reference for further research .